Early Surgical Intervention Results in Better Patient-Reported Outcomes Than Delayed Treatment in Patients Undergoing Anterior Cruciate Ligament Reconstruction in the Presence of Concomitant Medial Collateral Ligament Injury - Blake M. Bacevich, B.S.; Sean Hazzard, P.A., M.B.A.; Mia Lustig, B.S.; Saoirse Connelly, B.S.; Varun Nukala, B.S.; Peter Asnis, M.D. (Arthroscopy, Sports Medicine, and Rehabilitation)
Purpose: To investigate the influence of the timing of anterior cruciate ligament (ACL) reconstruction (ACLR) on patient-reported outcomes, comparing patients with and without concomitant medial collateral ligament (MCL) injury. Methods: This study included patients who underwent ACLR between September 2015 and October 2020. The inclusion criteria included patients for whom preoperative and postoperative patient-reported outcome measures were available and a follow-up period of at least 2 years. Patients who sustained grade 2 or 3 MCL injuries with ACL tears were compared with patients with no MCL injuries as a control. All patients underwent ACLR with either bone-tendon-bone autograft or bone-tendon-bone allograft. Patient-reported outcomes (International Knee Documentation Committee [IKDC] score, Lysholm score, and Knee Injury and Osteoarthritis Outcome Score [KOOS]) were recorded, and outcomes were analyzed by sex and time from index injury. A stratified linear mixed-effects regression analysis was conducted. Results: A total of 253 eligible patients with 2-year outcomes were enrolled. Patients with combined ACL-MCL injuries had lower IKDC scores (β = –6.1 vs β = –8.3, P = .003), KOOS Quality of Life values (β = –9.3 vs β = –11, P = .004), and KOOS Sport values (β = –12 vs β = –13, P = .08) if surgery was performed more than 6 weeks after the index injury. Patients with isolated ACL injuries showed lower KOOS Activities of Daily Living values (β = –2.4, P = .045) if surgery was performed at between 3 and 6 months. Among patients with combined ACL-MCL injuries, autograft was found to have worse IKDC scores (β = –11 [95% confidence interval (CI), –18 to –4.2]; P = .002), Lysholm scores (β = –9.2 [95% CI, –15 to –3.1]; P = .004), KOOS Quality of Life values (β = –11 [95% CI, –20 to –1.6]; P = .023), KOOS Pain values (β = –5.1 [95% CI, –10 to –0.03]; P = .049), KOOS Symptoms values (β = –7.6 [95% CI, –10 to –0.03]; P = .02), and KOOS Sport values (β = –21 [95% CI, –32 to –10]; P < .001) than allograft. Conclusions: Patients undergoing ACLR with grade 2 or 3 MCL injuries have improved patient-reported outcomes if surgery is performed within 6 weeks from the time of injury. In this cohort, allografts resulted in better outcome scores compared with autografts. Level of Evidence: Level III, retrospective cohort study.